Decision Support System for Selecting Optimal Coconut Varieties for Coconut Milk Production: Integration of Analytic Hierarchy Process and Simple Additive Weighting Methods - Hikam, Muhammad; Sari, Indah Purnama (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2024)
Selection of optimal coconut varieties for coconut milk production is a crucial step in the food industry, considering that the quality and quantity of coconut milk are greatly influenced by the type of coconut used. This study aims to determine the best coconut varieties for coconut milk production by integrating two multicriteria decision-making methods, namely the Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW). The AHP method is used to determine the weight of each influential criterion, such as oil content, taste, price, and availability. Meanwhile, the SAW method is applied to rank various coconut varieties based on the weight of the criteria that have been obtained. The data used in this study were collected from various sources, including scientific literature, as well as field observation data. The results of the analysis indicate that certain coconut varieties have significant advantages in terms of quality and efficiency of coconut milk production. The coconut varieties selected through the combined AHP and SAW methods are expected to provide practical guidance for coconut milk producers in selecting optimal coconut varieties, so that they can improve the quality of the coconut milk produced. Thus, this study provides an important contribution in the field of agribusiness, especially in the selection of coconut varieties for coconut milk production, as well as implementing the use of AHP and SAW methods in complex and multi-criteria decision making.